Analisis Biaya Pelatihan SDM - Doranda Putri Farid Nurkamiden; Mitha Nopelyn Soga; Astrid Rifai; Nabila Kasim; Adinda I. Sujono; Sintia Lawani; Sitti Annisa Y Panane; Sharina Putri Hurain (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study aims to analyze the employee training system at Toko Kue Hanania Food, particularly in improving product packaging skills and customer communication. Using the observation and documentation method, this research identifies that training is conducted through the On-the-Job Training method, where new employees learn directly in the workplace within one to three days. The results indicate that while this method is effective in accelerating employee adaptation, challenges such as lack of training documentation, limited trainers, and minimal evaluation and follow-up remain obstacles. Additionally, the company strives to manage training costs efficiently by utilizing internal resources and innovation in daily operations. To enhance training effectiveness, a more structured system is needed, such as the development of Standard Operating Procedures (SOPs) and providing incentives for employees who demonstrate performance improvements.